Cardiorespiratory fitness of medical students in a health institute in Eastern India - Sunil Kumar Jena (Wolters Kluwer Medknow Publications, 2020)
Background: VO2 max is the single most reliable indicator of cardiorespiratory fitness (CRF). More is the VO2 max more is the CRF and aerobic capacity of an individual. The status of CRF ultimately indicates the physical fitness. This study was conceptualized to estimate the CRF of medical students. Materials and Methods: This study included 161 apparently healthy participants, which included 101 male and 60 female MBBS students. The study was started after approval of the ethics committee. Each participant was clearly understood the study protocol and its output. Each participant signed the written consent form. Body weight was estimated without shoes and light clothing. The resting heart rate (RHR) was calculated by palpating radial pulse. VO2 max was determined by a predefined predicted equation using three factors, i.e., age, body weight, and RHR. VO2 max = 3.542+ (−0.014 × age in year) + (0.015 × body weight [kg]) + (−0.011 × RHR). Statistical analysis was done by unpaired test. Results: Mean VO2 max of male and female was 56.4 ± 4 and 51.9 ± 6 ml/kg/min, respectively. This difference was significant at P = 0.000. 26.7%, 28.7%, and 26.7% of males were good, excellent, and superior, respectively, in VO2 max. 13.3%, 8.3%, and 70% of females were good, excellent, and superior, respectively, in VO2 max. 21.7%, 21.1%, and 42.8% of total participants were good, excellent, and superior, respectively, in VO2 max. Conclusion: CRF of male was better than female. The majority of students' CRF was up to mark and minimal students need care to improve their CRF.